THE ANALYSIS AND IMPROVEMENT OF BUSINESS PROCESS BY USING BUSINESS PROCESS MODELLING NOTATION (BPMN) AT PT FASTRONIC MAKMUR SENTOSA (A CASE STUDY OF AN INDONESIAN TELECOMMUNICATION COMPANY) - Permata Putri Purwanto, Elvina
The usage of internet cellular data is essential for accessing related smartphone applications, such as social media. Indonesia is the eighth country with the highest usage of internet cellular data in the first quarter of 2021. This usage has been increasing due to the Covid-19 pandemic, with an increase of 3.7%. This means the telecommunication industry is growing. Regarding these facts, every huge telecommunication company in Indonesia has authorized dealers in every region to help the company in distributing the products. PT FMS is one of the authorized dealers of PT Smartfren Telecom Tbk for the Semarang area where this research is conducted. Established in 2004, the company started with selling phone credit balance and decided to be an authorized dealer of Smartfren in 2014. For daily business activity, there is already a software system for tracking every activity, but the system is not fully integrated between each other. However, PT FMS has not yet created a written business process, which is an important role in the business itself. Business process modeling is used to understand the key mechanism of an existing business, create appropriate information systems, improve the current business structure and operation, show the structure of an innovative business, identify outsourcing opportunities, and facilitate the alignment of business specifications with the technical framework. In this case, PT FMS needs to create a written business process as a form of visualization based on the existing business process. Additionally, the company needs to review and evaluate the business process to make it more efficient and effective.